Combinations of physical activity, sedentary behavior, and sleep and health outcomes in older adults: a systematic review protocol - Germano-Soares, Antonio Henrique (2021)
Recent systematic reviews highlighted important relationships between combinations of movement behaviors (ie. sleep, sedentary behaviour, and physical activity) and health outcomes among children and adolescents. However, it is unclear whether similar relationships occur in older adults. Therefore, the purpose of this protocol was to describe the aims and methods for a systematic review to summarize the studies examining the relationships between movement behaviors and health outcomes in older adults. A systematic review will be developed based on searches of articles in seven electronic databases and references of retrieved articles, contact with authors, and study repositories. Eligibility criteria: observational or experimental studies examining the association of at least two movement behaviours (sleep, sedentary behaviour, and physical activity) with health outcomes in older adults (≥60 years old). Selection of the studies and extraction of the data will be carried out by two reviewers independently. Characteristics of the study, participants, methods of combinations, and main results will be extracted and described. Risk of bias and level of evidence in the studies will be assessed according to the study quality tool of the US National Heart, Lung, and Blood Institute and the GRADE guidelines. The data will be synthesized using random effects meta-analysis for results that are sufficiently homogeneous in terms of statistical, clinical, and methodological characteristics. If not, then a narrative synthesis will be conducted. The results of this review may provide insights to improve current guidelines on 24-hour cycle in older adults, as well as guide future studies in this research field.